Host defense against the infection of Klebsiella pneumoniae: New strategy to kill the bacterium in the era of antibiotics? - Liang, Zihan; Wang, Yiyao; Lai, Yixiang; Zhang, Jingyi; Yin, Lanlan; Yu, Xiang; Zhou, Yongqin; Li, Xinzhi; Song, Yinhong (Frontiers in Cellular and Infection Microbiology, 2022)
Klebsiella pneumoniae (K. pneumoniae) is a typical gram-negative iatrogenic bacterium that often causes bacteremia, pneumonia and urinary tract infection particularly among those with low immunity. Although antibiotics is the cornerstone of anti-infections, the clinical efficacy of β-lactamase and carbapenems drugs has been weakened due to the emergence of drug-resistant K. pneumoniae. Recent studies have demonstrated that host defense plays a critical role in killing K. pneumoniae. Here, we summarize our current understanding of host immunity mechanisms against K. pneumoniae, including mechanical barrier, innate immune cells, cellular immunity and humoral immunity, providing a theoretical basis and the new strategy for the clinical treatment of K. pneumoniae through improving host immunity.